Regional Economic Policy Transition in the Local Government of Korea - Ki-yong Hong (European Regional Science Association (ERSA), 2003)
Regional economic policy in developing countries is dominated by central government. The potential of local government has recently attracted more interest (Eisiger 1988; Fosler 1988; Beckeman 1996; Jones 1990 ; Elkins 1966; Kossy; 1966; Leicht 1994). The general consensus is that local business climate manifests either entrepreneurial conditions. Since the early 1970s, local governments in Korea confine their policies for its diversification due to an incomplete financial environment. There has been increased public awareness that regional economic policies should be designed to give local authorities raising local organizational capacity as well as ensuring a greater equality in the allocation of funding and priorities. This study discusses regional economic policy and can summarize as follows; First, most local governments in Korea tend to adopt supply-led policies than the demanded one because of limited local resources and inexperience in its policy formulation/ implementation. Local government leaders, however, are increasingly aware of the importance of demand-led regional economic policy. This means that the entrepreneurial approach to economic development at the local level is being gradually imbedded after initiating local governance as a result of 1997 financial crisis in Korea. Second, the more wealthy, urban and industrial regions are the most innovative in every policy domain promoting regional economic development; this can be interpreted the urban areas have better access to financial/ human resources along with urban government officials having more experience in policy planning and implementation from their favorable resources. Third, there is a high correlation between policy environment factors and regional economic policy tools, particularly with the participation of private sector. The entrepreneurial approach to regional economic development is a crucial element in a firm's capability along with creation of the favorable business climate. Local governments with diverse regional economic policies tend to be associated with high government level and have more financial resources, expertise and a strong local leadership available to them. By contrast, the local governments with weaker regional economic programs are likely to be noted for poorer relationships with low level of policy environmental factor. Therefore, the central government needs to play a coordinated role of resource allocation for less favored regions in order to be diversify/ intensify regional economic development.
Keywords: 330